Pengembangan Sistem Penentuan Durasi Lampu Hijau Pada Lampu Lalu Lintas Menggunakan Fuzzy Logic - Yeo, Stefan; Tiffano Miracle Gaghana, Dave; Jason; Chandra Wijaya, Kevin; Stephen; Yulianto, Andik (Telcomatics, 2024)
Pavement is one of the most important aspects of the economy and everyday life in a city, as it is always used by people in their activities. The appearance of obstacles on the road can cause losses to both the economy and the quality of life of local residents. One form of obstacle that often appears on roads is traffic jams. This traffic jam can be caused by many things, ranging from the road condition, the number of vehicles, to a less than optimal red light system. This is where the application of fuzzy logic in a dynamic traffic light system can help to solve the problem.